Characterization of nanofluids in evaporating droplets by dynamic light scattering - Wu, Wenchang; Panduro Vela, David; Bück, Andreas; Fröba, Andreas Paul (Measurement, 2023)
The diffusion of nanoparticles in nanofluids in form of pendant drops and levitated droplets is characterized by dynamic light scattering. In combination with a heterodyne detection scheme, particle diffusivity in pendant drops can be determined by this method. The diffusivities therein correspond well to the values measured inside a cuvette. During evaporation, crust formation in the drop can also be identified by the method. Dynamic light scattering experiments for levitated droplets are performed with an ultrasonic acoustic levitator. Again, the dynamics of the particle number density fluctuations inside the droplet can be characterized, but the derivation of particle diffusivities is not yet possible. In both cases, the evolution of the characteristic time reflecting the diffusive process of nanoparticles can be determined until the point of crust formation. In summary, the applicability and limitation of dynamic light scattering for the characterization of diffusion of particles in evaporating drops are identifie
Keywords: Drying; Diffusion; Levitation; Dynamic light scattering; Pendant drop; Nanofluid

Spray Printing of Porous Substrates from Nanosuspensions - Panduro Vela, David; Schlumberger, Carola; Thommes, Matthias; Bück, Andreas (Processes, 2023)
In this work, we present and characterise an experimental setup that allows the generation of porous packings from nanosuspensions. By defined positioning and drying of solid-containing droplets, large-scale porous structures can be generated. Examples of such structures are shown and characterised. Operational challenges are presented, and it is discussed how they can be overcome to allow the maximum degree of freedom in packing generation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: drop-on-demand; drying; porosity; suspension; textural characterization